2021
DOI: 10.4014/jmb.2105.05032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus gasseri BNR17 on Postmenopausal Symptoms in Ovariectomized Rats

Abstract: Clinical and preclinical studies have reported that Lactobacillus gasseri BNR17, a probiotic bacterial strain isolated from human breast milk, reduces body weight and white adipose tissue volume. In order to further explore the actions of L. gasseri BNR17, we investigated the anti-menopausal effects of L. gasseri BNR17 in an ovariectomized (OVX) rat model. The serum alanine aminotransferase levels of the rats in the OVX-BNR17 group were lower than those of the rats in the OVX-vehicle only (OVX-Veh) group. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…Lactobacillus gasseri BNR17, a lactic acid bacterium, was isolated from human breast milk [15]. Our previous studies have shown that L. gasseri BNR17 has potential benefits in irritable bowel syndrome [16], weight control [17], type 2 diabetes [18], and alleviating menopausal symptoms [19]. However, no studies have assessed the anti-melanogenic and antioxidant activities of the cell-free supernatant from L. gasseri BNR17 (CFS).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus gasseri BNR17, a lactic acid bacterium, was isolated from human breast milk [15]. Our previous studies have shown that L. gasseri BNR17 has potential benefits in irritable bowel syndrome [16], weight control [17], type 2 diabetes [18], and alleviating menopausal symptoms [19]. However, no studies have assessed the anti-melanogenic and antioxidant activities of the cell-free supernatant from L. gasseri BNR17 (CFS).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the effect of probiotic treatment on bone formation, we examined the data from twenty-two selected articles that reported serum bone formation markers levels. Of these, six studies reported on serum osteocalcin (16,25,31,33,34,42) , seven studies on serum Ca (16,25,27,30,31,41,42) and six studies on serum ALP (27,29,30,34,40,41) . Pooled effect analysis was carried out using random effects model due to sufficient heterogeneity among studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, eleven studies each were conducted on mice and rats. All the eleven studies on rats used the strain Sprague Dawley (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . A total of 238 ovariectomised rats were used; 95 in control and 143 in experimental group.…”
Section: Design Of the Study And Parameters Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…OVX is a common method of inducing menopause in rats that reduces estrogen levels in serum. Hence, it is a prominent animal model for investigating female osteoporosis [ 24 ]. Several studies have demonstrated that a decrease in estrogen secretion increases dietary intake and white adipose tissue, resulting in metabolic obesity.…”
Section: Discussionmentioning
confidence: 99%